Validitas dan Praktikalitas Pengembangan Modul Digital Menggunakan Aplikasi Flip PDF Professional di Kelas IV - Putri, Amelisa; Reinita (Jurnal Elementaria Edukasia, 2023)
This exploration was driven by the use of printed textbooks in elementary schools that were less able to increase student participation, activeness and learning motivation. The presentation material used by the teacher has never used a computerized module using the Flip PDF Professional application. The purpose of this research was to develop a computerized module that involved the Flip PDF Professional Application in Learning Pancasila Education in Grade IV Elementary Schools. The research methods used are qualitative and quantitative methods. The model in this study uses the 4D model. The 4D model consists of four phases, namely: define, namely the needs analysis stage, design, namely designing digital modules, develop, namely by conducting validity and practicality tests, and disseminate the deployment stage. Data collection instruments include validity tests and practicality tests. The results of the validity test are 79% from a legitimate material perspective, 79% from a substantial language point of view, and 87% from a very legitimate media perspective. The results of the test for the fairness of the teacher's reaction obtained 92% results and student reactions obtained 94% results in the very feasible category. The conclusion of this study is that the Progress of Computerized Modules Involving the Flip PDF Professional Application in Grade IV Elementary Schools is stated to be very substantial, very reasonable and very interesting to use in the Pancasila educational experience.